Planetary Sensor Models Interoperability Using the Community Sensor Model Specification. Issue 6 (2nd June 2020) - Laura, J. R.; Mapel, J.; Hare, T.
Abstract: This paper presents the photogrammetric foundations upon which the Community Sensor Model specification depends, describes common coordinate system and reference frame transformations that support conversion between image sensor (charge‐coupled device) coordinates to some arbitrary body coordinate, and describes the U.S. Geological Survey Astrogeology Community Sensor Model implementation (https://github.com/USGS-Astrogeology/usgscsm ). We present a new image support data specification that provides the position, pointing, timing, and metadata information necessary to properly locate a pixel or observations location on a body and describe a system architecture designed to explicitly identify the responsibilities of software components within a larger pipeline or analytical environment. This paper concludes with a set of experiments that illustrate positional and pointing error in the sensor location and the impact on the computed surface location. Key Points: This paper describes the Community Sensor Model specification and demonstrates application to planetary science This paper presents an empirical sensor model error analysis and demonstrates that error is primarily attributable to errors in ephemeris